Finite photonic crystal waveguide with an embedded cavity: optical conductance “dips” and vortices - Albaladejo, Silvia (2011)
Light transmission through a finite photonic crystal waveguide with an embedded cavity is analyzed in terms of the optical conductance (OC). Under appropriate conditions, the transmission is inhibited for any angle of incidence. The resonance condition manifests itself as a dip in the OC. Just at the resonance, the power flow presentsstrong vortices inside the cavity.